141k views
4 votes
Which shows the equation below written in the form ax2 + bx + c = 0?

x + 10 = 3(x - 1)^2
A. 3x2 - 5x + 13 = 0
B. 3x2 -7x+ 13 = 0
c. 3x2-77-7 = 0
D. 3x2 - 5x- 7 = 0​

2 Answers

2 votes

Answer:

C

Explanation:

x+10=3(x2-2x+1)

x+10=3x2-6x+3

3x2-7x-7=0

User Danieltakeshi
by
5.4k points
5 votes

Answer:

3x² - 7x - 7 = 0

Explanation:

Given

x + 10 = 3(x - 1)² ← expand the factor

x + 10 = 3(x² - 2x + 1) ← distribute by 3

x + 10 = 3x² - 6x + 3 ( subtract x + 10 from both sides )

0 = 3x² - 7x - 7 or

3x² - 7x - 7 = 0

User Rams
by
4.2k points